Effects of high hydrostatic pressure on color, texture, microstructure, and proteins of the tilapia (Orechromis niloticus) surimi gels. Issue 2 (25th November 2020) - Lu, Wangwei; Qin, Yuyue; Ruan, Zheng
Abstract: The tilapia ( Orechromis niloticus ) surimi gels were prepared with high hydrostatic pressure (0, 100, 200, 300, and 400 MPa for 15 min) treatments to investigate the changes in water‐holding capacity, color, gel strength, microstructure, texture, and proteins of the gels. Compared it with cooked gel (40°C/30 min + 90°C/30 min). The whiteness of heat‐induced and HHP‐induced gels were significant ( p  < .05) higher than that of untreated samples. The gels formed by pressurization were dense and flexible, and formed by cross‐linking based on hydrogen bonding. SDS‐PAGE patterns showed no major change in the actin and tropomyosin protein profiles of gels induced by HHP‐300. Raman spectroscopy confirmed disulfide bonds played an important role in gel formation. A lower intensity ratio observed in HHP‐induced protein supported the tyrosine residues involved in hydrogen bond formation. The changes of secondary structure suggested decreased α ‐helix content and increased β ‐sheet.